Tenigblikke op die Fakulteit Teologie (Afd A), Universiteit van Pretoria, en sy lede - "n literatuurverkenning - Oberholzer, J. P. (Hervormde teologiese studies, 1992)
Retrospection on the Faculty of Theology (Sec A), University of Pretoria, and its members - a survey of literature A short, selective survey of literature on the motives for the founding of the Faculty of Theology (Sec A), University of Pretoria, and its history is given. Special attention is given to the typification of the theology of Faculty members by recent writers.